Success Story... Starting a roof top gardening - Singh, P K; Janakiram, T; Patel, Neelam (Indian Horticulture, 2019)
This all began when Mr O P Sharma, a retired officer from GAIL (India) in 2010, created his own niche in rooftop farming. His love for plants re-emerged due to changing priorities. He became a homemaker and now leading a happy and relaxed retired life. He is a successful farmer.